2019
DOI: 10.21608/resoncol.2019.11625.1076
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics and Survival of Triple-Negative Breast Cancer Patients: A single Institution Study from Egypt

Abstract: Background: Triple-negative breast cancer (TNBC) is a subtype of breast cancer that is characterized by being more aggressive, presentation in younger age, and higher response rate to chemotherapy. It is more likely to recur and to metastasize early. Methods: Retrospective review of the medical records of TNBC patients treated in a single Egyptian cancer center during a 4-year period. Results: Sixty-five patients were included. Forty-six percent of patients were < 50 years old and 22% had a positive family his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Makar, (2019) reported that the most common histopathological type was IDC and approximately one third of the patients had grade III tumor. 19 According to the NCCN guidelines in oncology, 2018; 92.5% were in stage II. Similar results were reported by a previous study in Egypt; Gihan et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Makar, (2019) reported that the most common histopathological type was IDC and approximately one third of the patients had grade III tumor. 19 According to the NCCN guidelines in oncology, 2018; 92.5% were in stage II. Similar results were reported by a previous study in Egypt; Gihan et al (2019).…”
Section: Discussionmentioning
confidence: 99%